Creating realistic scenarios in teaching speaking skill through virtual English camp Covid 19 - Hengki Hengki; Ratna Ratna (Journal of English Language Teaching and Learning (JETLE), 2022)
The purpose of this study is to determine whether creating realistic scenarios (CRS) for teaching speaking skills through a Virtual English Camp is beneficial in improving students' speaking skills (VEC). Determine the impact of generating a realistic scenario through VEC on improving the capacity of English major students to deliver speeches, participate in public speaking events, participate in discussions, and participate in the debate. This study is an experiment involving a one-group pre-test and post-test design, as well as a survey design to determine the overall average of the scores. The participant of this study is 145 college students of English Majors from South Kalimantan, Indonesia. They put out a significant effort to improve their communication skills. Their trainer trained them and compelled them to refrain from acting as a language instructor during the discussion program, and instead to speak in the target language, which was English, throughout the program. During this study, it was found that students who were taught with VEC thereafter had higher post-test scores than students who were taught before they were tested for their communicative competence. Students' communicative competence increases significantly when they participate in the VEC model program to teach them speaking abilities.